2019
DOI: 10.1080/15532739.2019.1652129
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of gender diverse and trans children and youth considering and initiating medical interventions in Canadian gender-affirming speciality clinics

Abstract: Background : Canadian specialty clinics offering gender-affirming care to trans and gender diverse children and youth have observed a significant increase in referrals in recent years, but there is a lack of information about the experiences of young people receiving care. Furthermore, treatment protocols governing access to gender-affirming medical interventions remain a topic of debate. Aims: This qualitative research aims to develop a deeper understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 40 publications
1
101
0
2
Order By: Relevance
“…Overall, and as expected, transgender young people and their parents received more informed and affirming care from dedicated gender clinics than from broader healthcare services. Largely positive experiences of care in gender clinics reflects the existing limited number of studies with young people and their families in Australia (Tollit et al, 2019), Canada (Pullen Sansfaçon et al, 2019), and the US (Inwards-Breland et al, 2019). Receiving such care is particularly important for those accessing medical treatment (puberty blockers and hormones).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, and as expected, transgender young people and their parents received more informed and affirming care from dedicated gender clinics than from broader healthcare services. Largely positive experiences of care in gender clinics reflects the existing limited number of studies with young people and their families in Australia (Tollit et al, 2019), Canada (Pullen Sansfaçon et al, 2019), and the US (Inwards-Breland et al, 2019). Receiving such care is particularly important for those accessing medical treatment (puberty blockers and hormones).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of strengths, professionals who are supportive, knowledgeable, and, respectfulincluding by using correct names and pronounsare experienced as affirming (Corliss, Belzer, Forbes, & Wilson, 2007;Guss et al, 2019;Riggs, Bartholomaeus, & Pullen Sansfaçon, 2020;Strauss et al, 2017). Experiences of such affirming responses have been related to high levels of satisfaction among young people and their families attending paediatric gender clinics (Inwards-Breland et al, 2019;Pullen Sansfaçon et al, 2019;Tollit, Feldman, McKie, & Telfer, 2019). In terms of limitations, research has identified a lack of understanding by healthcare professionals of transgender young people's needs, discrimination, misgendering, and a lack of training about gender diversity (Carlile, 2020;Corliss et al, 2007;Eisenberg, McMorris, Rider, Gower, & Coleman, 2020;Goldenberg et al, 2019;Gridley et al, 2016;Guss et al, 2019;Heard et al, 2018;Strauss et al, 2017;Temple Newhook, Benson, Bridger, Crowther, & Sinnott, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the research protocol of a pan-Canadian qualitative research project, “Stories of gender affirming care: learning from children, youth and their families,” we adapted the data collection tools to the Swiss context to provide baseline data for future comparison (Pullen Sansfaçon et al funded by CIHR 2016–2019). The Canadian project examines the experiences of gender diverse and transgender children and youth and their parents/caregivers who have been referred to gender affirmative clinics.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…Literature on coming out and gender identity shows that the development of a transgender or gender diverse identity appears on average between the ages of five and eight (Olson and al., 2011). But disclosure to the family and social circle generally occurs years later (Olson and et al, 2015; Riggs, 2019; Pullen Sansfaçon et al, 2019). This huge gap produces a long period of secrecy and sometimes isolation where communication in the family is not optimal.…”
Section: Introduction: Trans Youth and Their Families Becoming Visiblementioning
confidence: 99%
“…12 In addition, although a cause-effect relationship has not been established, an association between later presentation to GAMC and worse mental health among genderincongruent youth has been identified. 2 Barriers to GAMC 13,14 as well as the care-seeking experiences [15][16][17] and decision-making processes 18,19 of gender-incongruent youth have been described. However, the important questions of whether genderincongruent youth who present for GAMC at older ages have different care-seeking experiences or face different barriers than youth who present younger have not been addressed.…”
mentioning
confidence: 99%